Evidence-based emergency care diagnostic testing and clinical decision rules - Pines, Jesse M. (Chichester, West Sussex : Wiley, 2013)
"The purpose of this book is to present relevant questions on diagnostic testing that arise in everyday emergency medicine practice and to comment on the best available evidence"--Provided by publisher.
Machine generated contents note: About the AuthorsForeword - Jeffrey KlinePreface to Second EditionSection 1: The Science of Diagnostic Testing and Clinical Decision Rules1 Diagnostic Testing in Emergency Care2 Evidence-Based Emergency Care: The Process 3 The Epidemiology and Statistics of Diagnostic Testing4 Clinical Decision Rules 5 Appropriate Testing In an Era of Limited Resources: Practice and Policy Considerations6 Understanding Bias in Diagnostic Research Section 2: Trauma7 Cervical Spine Fractures8 Cervical Spine Fractures in Children 9 Cervical Spine Fractures Older Adults10 Blunt Abdominal Trauma11 Acute Knee Injuries12 Acute Ankle and Foot Injuries13 Blunt Head Injury in Children14 Blunt Head Injury15 Blunt Chest Trauma16 Occult Hip Fracture17 Blunt Soft Tissue Neck Trauma18 Occult Scaphoid Fractures19 Penetrating Abdominal Trauma20 Penetrating Trauma to the Extremity and Vascular Injuries Section 3: Cardiology 21 Heart Failure 22 Syncope23 Acute Coronary Syndrome 24 Palpitations Section 4: Infectious Disease 25 Bacterial Meningitis In Children26 Serious Baterial Infections in Children Aged One to Three Months27 Necrotizing Fasciitis28 Infective Endocarditis29 Pharyngitis30 Rhinosinusitis 31 Pneumonia32 Urinary Tract Infection33 Sepsis34 Septic Arthritis35 Osteomyelitis36 Sexually Transmitted Diseases37 Influenza38 Pediatric Fever Section 5: Surgical and Abdominal Complaints 39 Acute, Non-specific, Non-traumatic abdominal pain40 Small Bowel Obstruction41 Acute Pancreatitis42 Acute Appendicitis43 Acute Cholecystitis44 Aortic Emergencies45 Ovarian torsion Section 6: Urology 46 Nephrolithiasis47 Testicular torsionSection 7: Neurology 48 Non-traumatic Subarachnoid Hemorrhage49 Acute stroke50 Transient Ischemic Attack51 Seizure Section 8: Miscellaneous: Ophthamology, Hematology, Rheumatology, and Pulmonology 52 Venous Thromboemoblism53 Temporal arteritis54 Intraocular pressure55 Asthma56 Non-traumatic Back Pain57 Intravascular Volume Status58 Geriatric syndromesIndex.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Emergency medicine -- Diagnosis; Emergency medicine -- Decision making; Evidence-based medicine; Electronic books